Effectiveness of circuit training in physical education classes on Health Related Fitness (HRF) and Motor Skill Competence (MSC) among primary schools’ obese children - Abdul Razak, Zaharul Azwan; Hasan, Hosni; Tan, Chee Hian; Ong, Tah Fatt (Faculty of Sports Science and Recreation, 2024)
Physical Education is one of the compulsory subjects in the Malaysian educational system and widely lacking in the process of teaching and learning, because of different approaches implemented by various schools’ teachers and it needed to venture as far as this pillar of our National Education. The purpose of this study was to investigate the effectiveness of Circuit Training (CT) on obese students’ specifically their health-related fitness (HRF) and motor skill competence (MSC) which is in line with the rise of obesity rate among young children nationwide. Pre and post-test with a total of 232 obese primary students who were randomized and assigned into control and experimental groups for age group 8 and 11 years old respectively. Descriptively, significantly the effectiveness of CT on obese students’ body weight and even BMI index decreased for the experiment group for both age groups (31.08 kg/m2 to 30.93 kg/m²) but not in control groups. Thus, body weight increased in control groups (49.92 kg to 50.07 kg). HRF consisted cardiovascular, strength, endurance and flexibility showed clear results of the CT implemented especially in both groups' ages with enhancing better scores in all components (101.62 to 108.03, 5.69 to 6.59, 7.26 to 8.40, and 24.77 to 24.80 minutes separately) compared to control groups. Moreover, there were some cardiovascular and flexibility increases after 8 weeks. Hence, obese 11-year-old students showed impressive enhancing reading for all HRF. However, in the 11-year-old control groups, there was an increase in cardiovascular only and a decrease in the rest. Where else, the motor skill competencies for 8 weeks decreased in competencies of running, kicking, jumping and throwing but vice versa for the experimental groups. CT is an appropriate teaching approach in PE for MSC and HRF during primary schools as far as student-centred approaches are concerned.